The Impact of Paulownia Leaves Extract on Performance, Blood Biochemical, Antioxidant, Immunological Indices, and Related Gene Expression of Broilers - Sakr, Shimaa A.; EL-Emam, Huda A.; Naiel, Mohammed A. E.; Wahed, Noha M.; Zaher, Hanan A.; Abougabal, Mohammed Sh.; Alghamdi, Youssef S.; Albogami, Sarah; Soliman, Mohamed Mohamed; Shukry, Mustafa; Elghareeb, Mona M. (Frontiers in Veterinary Science, 2022)
Paulownia leaves are a rich source of bioactive chemicals and have a good influence on animal health when used as a new alternative feed ingredient for various livestock. Therefore, this study aimed to assess the impact of paulownia leaves extract (PLE) on performance, blood hematology, antioxidant activity and immune response of broiler chickens. Two hundred one-day-old mono-sexed Cobb500 chicks were randomly allocated into four equal groups with 5 replicates. The first group served as a control (CNT) and was fed the basal diet only, whiles the second, third and fourth groups were fed on the basal diet supplemented with 0.1, 0.3 and 0.5 g/kg diet of PLE, respectively. The performance results showed significant increments in live body weight (LBW), weight gain (WG) and EPEI in cooperated with increasing PLE level in broiler diets. At the same time, feed conversion ratio (FCR) and livability percentages were numerically enhanced under the effects of PLE supplementation. Moreover, dietary PLE administration did not induce any negative effects on blood biochemical parameters. In addition, a notable increase in oxidative remarks activity (GSH, SOD and CAT) and elevated levels of immunoglobulin (IgM and IgG) was noted for groups fed with PLE in a dose-dependent manner. Also, a dramatic linear increase was observed in mRNA expression of IGF-1, GHR, IL-1β and IL-10 genes of broiler chickens. Conclusively, this study recommended that enriched broiler diets with 0.5 g/kg PLE could be recommended as a safe phytogenic feed additive to promote growth, enhance antioxidant activity and boost immunity on broiler.